1996
DOI: 10.1177/0361198196153000107
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rubber and Asphalt Binders by Depolymerization and Devulcanization of Scrap Tires in Asphalt

Abstract: Scrap tires in three forms—crumb rubber 60 minus mesh, crumb rubber 20 minus mesh, and buffed rubber—were subjected to depolymerization and devulcanization by applying heat, high shear, and a combination of both. Different reaction temperatures and times of reaction were applied. The reaction products were submitted to the testing of rheological properties by measurement of creep and recovery, viscosity, and some conventional tests. The amount of unreacted rubber and tendency to separation during the hot stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 2 publications
1
34
0
1
Order By: Relevance
“…By contrast, values lower than 1, as that found for crumb tire rubber-modified bitumen, point out the precipitation of nondissolved rubber particles, that increases crumb rubber concentration at the bottom of the test tube. Settling of rubber particles and creaming of polymers in modified bitumen samples are common problems mentioned in several studies [13,14,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, values lower than 1, as that found for crumb tire rubber-modified bitumen, point out the precipitation of nondissolved rubber particles, that increases crumb rubber concentration at the bottom of the test tube. Settling of rubber particles and creaming of polymers in modified bitumen samples are common problems mentioned in several studies [13,14,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies focusing on CR modified asphalt binder were then carried out. Previous studies reported that CR significantly increase the mechanical properties of asphalt binder [31,32,33]. By applying CR powders, both the high and low temperature performance of asphalt binder can be significantly enhanced [22,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a 3000 rpm interaction speed has the potential to result in a more homogenous asphalt-rubber binder [16,17]. The CRM was difficult to entirely dissolve in asphalt due to its cross-linked structure [18]. Nevertheless, the above-mentioned specific interaction parameters were proven to be attributed to the formation of a 3D network structure, which was significantly effective in terms of the binder rheological properties enhancement [19].…”
Section: Crm As An Asphalt Modifiermentioning
confidence: 99%